2017
DOI: 10.1007/s10147-017-1181-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for disease-free and overall survival of patients with uterine carcinosarcoma

Abstract: Lymph node metastasis is the most significant prognostic factor associated with poor DFS and OS in UCS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
2
4
1
Order By: Relevance
“…A percentage range of 40-46 and 30-45% has been reported for leiomyosarcomas carcinosarcomas, respectively. In contrast to these findings, the range and percentage was estimated to 86-97% for ESSs and to 69% for adenosarcomas, respectively (20,(26)(27)(28). The rates reported in the present study were lower than those previously published.…”
Section: Uterine Sarcomas By Histological Type ----------------------contrasting
confidence: 99%
“…A percentage range of 40-46 and 30-45% has been reported for leiomyosarcomas carcinosarcomas, respectively. In contrast to these findings, the range and percentage was estimated to 86-97% for ESSs and to 69% for adenosarcomas, respectively (20,(26)(27)(28). The rates reported in the present study were lower than those previously published.…”
Section: Uterine Sarcomas By Histological Type ----------------------contrasting
confidence: 99%
“…However, a study published by Şükür et al demonstrated that LNM was the most important predictor of UCS survival in a multivariate analysis. 19 The Cox model identified an independent negative association between older age and OS but not CSS, which suggests that the elderly with OCS may die of other diseases or causes rather than OCS. Subgroup analysis revealed that LNM had an impact on CSS and OS in AJCC T2 (CSS, HR = 3.62, 95% CI = 1.50–8.73; OS, HR = 3.71, 95% CI = 1.59–8.68) but not AJCC T1 (CSS, HR = 1.78, 95% CI = 0.50–6.37; OS, HR = 1.97, 95% CI = 0.61–6.39).…”
Section: Discussionmentioning
confidence: 91%
“…Chen et al evaluated 81 patients and reported that advanced age was a significantly worse prognostic factor in terms of both OS and PFS 20 . There are also studies in the literature stating that age has no prognostic value in carcinosarcomas [11][12][13] . Worse DFS in advanced age could be attributed to the better response to adjuvant treatment in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rhabdomyosarcoma is the most common heterologous component, followed by chondrosarcoma, osteosarcoma, and liposarcoma 1 . A consensus has emerged in UC regarding some prognostic factors such as stage, lymphadenectomy, residual disease, and adjuvant therapy that affect survival 6 , 10 , 12 , 13 . In this study, which was conducted in a tertiary reference center with more than 20 years of experience in the field of gynecological oncology, we found that the presence of a heterologous component in UC shortened both OS and DFS compared with the presence of a homologous component.…”
Section: Discussionmentioning
confidence: 99%